Parasites and their utilization in aphid control in the tropics (Hymenoptera: Aphidiidae, Homoptera: Aphidoidea) - Stary, Peter (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
An overview of aphid parasites and their role in aphid control in the tropics is presented. The current state of research on parasites in the tropics is somewhat low, while their use as control agents appears promising. Research on this group, equivalent to that conducted on parasitic faunas in other regions, is recommended.